2020
DOI: 10.1021/acssuschemeng.0c07531
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Functionalized Cellulose Nanofibrils for Improving Triboelectric Charge Density of a Triboelectric Nanogenerator

Abstract: Excellent triboelectric charge density and hydrophobicity are achieved on cellulose nanofibrils (CNFs) by employing a simple and environmentally friendly approach to aminosilane modification of a CNF film. The positive charges on the CNF surface obtain gigantic enhancement, and a CNF-based triboelectric nanogenerator (TENG) with enhanced performance and moisture resistance is prepared. The performance of this functional CNF-based TENG can show outstanding output stability when the environmental humidity is 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 44 publications
0
54
0
Order By: Relevance
“…modified CNF with the amino group by eco‐friendly grafting of 9‐(2‐aminoethylamino)‐propyldimethoxymethylsilane (AEAPDMS) on the CNF (A‐CNF). [ 96 ] Figure 19B illustrates the A‐CNF TENG prepared with the FEP as an opposite triboelectric layer. The A‐CNF TENG produced an output voltage, current and charge of 195 V, 13.4 µA, and 65 nC.…”
Section: Natural Materialsmentioning
confidence: 99%
“…modified CNF with the amino group by eco‐friendly grafting of 9‐(2‐aminoethylamino)‐propyldimethoxymethylsilane (AEAPDMS) on the CNF (A‐CNF). [ 96 ] Figure 19B illustrates the A‐CNF TENG prepared with the FEP as an opposite triboelectric layer. The A‐CNF TENG produced an output voltage, current and charge of 195 V, 13.4 µA, and 65 nC.…”
Section: Natural Materialsmentioning
confidence: 99%
“…Nie et al performed simple aminosilane modification on CNFs and prepared an A-CNFs-based flexible TENG with increased frictional charge density. Figure 8 a shows the structure of TENG using A-CNFs film as the contact material and the working principle of TENG based on A-CNFs [ 161 ]. It was found that the voltage of TENG based on A-CNFs can be maintained at an almost constant level within 10,000 cycles, which indicated that its output performance was relatively stable and can provide sufficient voltage for electronic devices.…”
Section: Applications Of Cellulose Nanopapermentioning
confidence: 99%
“…
Fig. 8 a Structure of a TENG that uses the A-CNFs film as a contact material, working principle of the A-CNFs-based TENG, and stability and durability test of the TENG after 10,000 cycles [ 161 ]. b Performance comparison of pure PDMS and PDMS/CNCFs, and illustration of the triboelectric contact electrification processes with the net electric field E in composite films along the direction from the PDMS to the top Al electrode [ 162 ].
…”
Section: Applications Of Cellulose Nanopapermentioning
confidence: 99%
“…At the same time, the content of C1s continued to increase, and the contents of O1s and O/C continued to decrease. This was because ethylenediamine destroyed the epoxy group of epichlorohydrin, grafted to the sample surface, and introduced a large amount of C (Junka et al, 2014;Nie et al, 2020).…”
Section: Characterizationmentioning
confidence: 99%